Suicide Attempt in Schizophrenia - Harikha, Igha Vinda; Nalini Muhdi; Tiwik Koesdiningsih (Jurnal Psikiatri Surabaya, 2022)
Suicide is a very important sosial phenomenon and requires attention not only from psychiatrists but also the general public. The phenomenon of suicide has spread to almost all parts of the world, both in countries with advanced technology and in developing countries, from rich countries to poor countries. The risk of suicide among people with schizophrenia is higher than the general population. Attempted suicide is an act of self-injury that is done intentionally and aims to die, but does not cause death. These actions represent psychological difficulties and there are several risk factors associated with suicide attempts. Schizophrenia is a chronic and severe psychiatric disorder with a huge global health burden. Among those suffering from schizophrenia, the lifetime suicide rate is around 5% and suicide is the leading cause of premature death.Keywords: Suicide, Suicide Attempt, Schizophrenia